Experimental Demonstration of an Indoor VLC Positioning System Based on OFDMA - Bangjiang Lin; Xuan Tang; Zabih Ghassemlooy; Chun Lin; Yiwei Li (IEEE Photonics Journal)
We propose an indoor visible light communication (VLC) and positioning system using the orthogonal frequency division multiplexing access (OFDMA) scheme, which can provide both indoor positioning and communications. Three subcarriers with the maximum received signal intensity with respect to three light-emitting diodes (LEDs) are selected for indoor positioning based on the trilateration algorithm. The experiment results show that the proposed system with quadrature phase shift keying (QPSK) mapping offers a mean positioning error and an error vector magnitude of 1.68 cm and more than 15 dB, respectively.